PENGARUH KOMPENSASI, KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN CV. JADE INDO PRATAMA MALANG - Khoirul Anwar; Hadi Sunaryo; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT         This study aims to examine and analyze the effect of compensation, organizational commitment and work motivation on the performance of CV employees. Jade Indo Pratama Malang both partially and together. The population is 130 employees and a sample of 40 people. Data collection through questionnaires. Data analysis in this study uses SPSS version 16. The sampling technique using quantitative methods and data testing techniques used in this study include validity test, reliability test, classic assumption test and multiple linear regression analysis, and testing the research hypothesis.       The results of the analysis show that partially compensation does not have a significant effect on employee performance and organizational commitment does not significantly influence employee performance while work motivation has a significant effect on employee performance. Together, it shows that compensation, organizational commitment and work motivation significantly influence employee performance.Keywords: Compensation, Organizational Commitment, Work Motivation and Employee Performance.